2020
DOI: 10.1371/journal.pntd.0008788
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthetic DNA vaccine elicits protective immune responses against Powassan virus

Abstract: Powassan virus (POWV) infection is a tick-borne emerging infectious disease in the United States and North America. Like Zika virus, POWV is a member of the family Flaviviridae. POWV causes severe neurological sequalae, meningitis, encephalitis, and can cause death. Although the risk of human POWV infection is low, its incidence in the U.S. in the past 16 years has increased over 300%, urging immediate attention. Despite the disease severity and its growing potential for threatening larger populations, current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…We have developed a novel VLP-based vaccine candidate against the tick-borne POWV. To date, only two nucleic acid-based vaccine candidates have been developed against Powassan infection, each exhibiting some efficacy and safety [29,30]. However, RNA-based vaccines require stringent cold chain maintenance for storage and distribution, whereas VLPs are quite stable under standard refrigeration, potentially facilitating the distribution.…”
Section: Discussionmentioning
confidence: 99%
“…We have developed a novel VLP-based vaccine candidate against the tick-borne POWV. To date, only two nucleic acid-based vaccine candidates have been developed against Powassan infection, each exhibiting some efficacy and safety [29,30]. However, RNA-based vaccines require stringent cold chain maintenance for storage and distribution, whereas VLPs are quite stable under standard refrigeration, potentially facilitating the distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the POWV 351–359 region containing a CD8 + T cell epitope also contains an POWV-specific B cell epitope identified by Choi et al (2020) in their synthetic enhanced DNA-based POWV vaccination approach ( Choi et al, 2020 ). These concomitant findings, as well as other studies ( Cimica et al, 2021 ), underscore the benefit of a VLP-based vaccination strategy that elicits responses to B and T cell epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…A high proportion (>50%) of reported POWV infections are accompanied by long-term neurological sequelae, which range in severity from mild to debilitating ( Hermance and Thangamani, 2017 ; Kemenesi and Bányai, 2019 ; Goldfield et al, 1973 ; Tavakoli et al, 2009 ) and in 10%–15% of cases is fatal ( Kemenesi and Bányai, 2019 ; Tavakoli et al, 2009 ). Although nucleic acid-based vaccination approaches can prevent severe disease and neurological sequelae in murine models of POWV infection ( Choi et al, 2020 , Vanblargan et al, 2018 ), there are no approved vaccines or therapeutics for individuals infected with POWV. Currently, there are six approved vaccinations for the flavivirus tick-borne encephalitis virus (TBEV) that can prevent the development of severe disease and neurological sequelae ( Chernokhaeva et al, 2016 ; Chumakov et al, 1963 ; Kubinski et al, 2020 ), but these vaccines are not effective in preventing POWV infection ( Chernokhaeva et al, 2016 ; Shamanin et al, 1991 , Mcauley et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have evaluated potential POWV vaccines. Both a lipid nanoparticle (LNP)-encapsulated modified mRNA vaccine and a synthetic DNA vaccine encoding the POWV prM and E genes elicited potently neutralizing antibodies in serum and conferred protection in lethal challenge models in mice [ 29 , 30 ]. Another study demonstrated that a POWV virus-like particle (VLP), which also included the POWV prM and E genes, elicited strong neutralizing antibody responses [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work toward POWV vaccine development, which includes the investigation of mRNA [ 29 ], DNA [ 30 ] and VLP [ 31 ] platforms, has focused on the presentation of POWV prM and E proteins as the antigen. While these platforms have demonstrated the induction of neutralizing and protective antibody responses in mice, the full prM and E proteins contain many antigenic sites, only a subset of which are targets of functional antibodies that limit POWV infection.…”
Section: Introductionmentioning
confidence: 99%